Scientific and technical guidance for the preparation and presentation of a health claim application (Revision 2). (31st January 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: EFSA asked the Panel on Dietetic Products, Nutrition and Allergies (NDA) to update the scientific and technical guidance for the preparation and presentation of an application for authorisation of a health claim published in 2011. Since then, the NDA Panel has gained considerable experience in the evaluation of health claims. Lessons learnt from these experiences have been translated into a new General scientific guidance for stakeholders on health claim applications (published in January 2016). In this context, it is noted the need to adapt the existing guidance to the new scientific and technical developments in this area. This guidance document presents a common format for the organisation of information for the preparation of a well‐structured application for authorisation of health claims which fall under Articles 13(5), 14 and 19 of Regulation (EC) No 1924/2006. This guidance outlines the information and scientific data which must be included in the application, the hierarchy of different types of data and study designs, and the key issues which should be addressed in the application to substantiate the health claim. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1159/full